Fundamental Knowledge on Forgotten Species - Descovich, Kris (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dear Colleagues, Zoological institutions contribute a large amount of fundamental and applied knowledge on a diverse array of animal species. Despite this significant contribution, research conducted within zoos or other captive wildlife facilities has historically been skewed toward charismatic mammals, which comprise only a small proportion of the species that are held in captive collections. Modern zoos play an important role in animal welfare, conservation, and environmental education; therefore, this shortfall in knowledge may have large, unseen, and negative impacts on these “forgotten species”. Hypothesis-driven, experimental research plays a key role in filling these knowledge gaps; however, other avenues of data collection exist which may be equally important. These include observational data (collected without experimental interventions), operational data (data collected within the general management activities of a facility), and incidental data (data collected for one purpose which may reveal further important information when explored in more detail). These unpublished datasets may provide fundamental information on species for which comparatively little is known.